Peculiar Aspects of Narration of Ḥadīths in "Ru’ūs Al-Masā’il" - S. S. Saidjalolov (International Journal of Formal Education, 2024)
Maḥmūd Zamakhsharī is a great mufassir, mutakallim, jurist who came from Movarounnahr. When the scientific, cultural and economic situation in Mā Warāʾ al-Nahr was in decline, Maḥmūd Zamakhsharī served to revive and restore science, specially in Qur’ān, ḥadīth and fiqh studies with selfless scientists. Ten of his works are known today, and scientific researches on these works continue without stopping. This articles mainly contributed to aspects of narration of ḥadīths in Ru’ūs al-masā’il manuscript.